One-year outcomes of unipolar depression patients with manic or hypomanic switch during acute antidepressant treatment. (August 2013) - Wada, Ken; Sasaki, Takanobu; Jitsuiki, Hiroaki; Takaishi, Yoshiyuki
Abstract: Objective . The aim of the study was to investigate one-year outcomes of unipolar depression patients with manic or hypomanic switch during acute antidepressant treatment. Methods . A review of medical records revealed 37 consecutive patients admitted from 1997 to 2002 who underwent an antidepressant-induced manic or hypomanic switch fulfilling DSM-IV criteria. Their clinical courses were retrospectively investigated after discharge. Results . Of the 37 patients, 33 (89.2%) were followed up for 1 year after discharge. None developed a manic episode, while seven developed a hypomanic episode, including 1 patient who was lost after emerging from a hypomanic episode within 6 months after discharge. Only one of those seven patients developed hypomania during acute antidepressant treatment for a recurrent depressive episode under maintenance mood stabilizer treatment. Furthermore, bipolar conversion occurred in four patients within the first 6 months and in another two patients, including 1 with rapid cycling, over the subsequent 6 months after discharge. Of these 33 patients, 28 received continuous maintenance treatment with mood stabilizers for the one-year period after discharge. Conclusions . The subjects were considered to have a bipolar nature according to the prevalence rate of bipolar conversion over a one-year period. Longer follow-up studies appear warranted determine the diagnostic issues of antidepressant-induced switch in unipolar depression.